The Impact of Cerebral Microinfarction on Blood-Brain Barrier Permeability and Behaviour in Mice - Filadelfi, Melissa (Université d'Ottawa / University of Ottawa, 2020)
From mid- to late-life aging, many individuals acquire hundreds or even thousands of tiny strokes, known as microinfarcts. These lesions are not apparent using conventional neuroimaging and are therefore primarily detected through histopathological analysis. Notably, clinical and preclinical researchers are unsure of how cerebral microinfarction impacts the brain’s vasculature and its effect on motor output. This thesis aims to characterize a mouse model of cerebral microinfarction to assess the impact of these microscopic lesions on blood-brain barrier (BBB) integrity and motor behaviour. For the first experiment, mice were unilaterally injected through the left common carotid artery with GFP microspheres (20 µm) and were sacrificed at different time points post-surgery (days 1, 3, 7, 14, and 21). All mice received an intravascular injection of Evans Blue dye (100 µl) through the tail vein thirty minutes prior to being transcardially perfused in order to evaluate BBB extravasation, a measurement of BBB disruption. To evaluate motor performance post-microinfarction, sham and microinfarct mice underwent a battery of behavioural tasks prior to and post-surgery. Cerebral microinfarction resulted in acute BBB disruption, where albumin leakage was most prominent one day following surgery. With our microinfarct mouse model, a Python script was developed to semi-automatically detect and register the microspheres to specific brain regions using the Allen Mouse Brain Atlas (version 3). Additionally, using several gross and fine motor behavioural tasks, analyses performed across both experimental groups revealed no significant motor impairments. Having a better insight into how these microscopic lesions affect brain structure and function in preclinical models would increase our understanding of how cerebral microinfarction impacts the human brain.
Keywords: Cerebral microinfarction; Blood-brain barrier; Behavioural performance